Photodegradation of biopolymer doped with titanium dioxide (TiO2) as ultraviolet (UV) stabilizer - Mohid, Siti Rahmah (2015)
A large amount of waste cooking oil has become an environmental issue around the world. This oil is renewable and biodegradable than the corresponding products made from petroleum sources. The major concern in this study focuses on the resistance of the biopolymer to ultraviolet (UV) light exposure. The virgin oil (VO) and waste oil (WO) was converted into biomonomer. By adding biomonomer with an appropriate amount of 4, 4’-methylene diphenyl diisocyanate (MDI) and solvent, the virgin oil polymer (VOP) and waste oil polymer (WOP) were produced. The biopolymer (BP) were added with low loading metal oxide filler which is 2.5, 5, 7.5 and 10 % of titanium dioxide (TiO2) to form biopolymer composite (BPC). The resistance to UV light and mechanical properties of BP and BPC were determined after exposure the thin films in UV weatherometer for an extended period of time at 250, 500, 750,1000, 2000 and 3000 hours. The results based on the spectroscopic analysis of UV-Vis and FTIR confirmed the photodegradation processes of BP and BPC of VOP and WOP. The increasing absorbance in UV-Vis spectra indicated the formation of quinone after UV-irradiation of BP and BPC of VOP and WOP. Furthermore, BP thin films shows rapid loss of tensile strength but the increased loading of TiO2 can improve mechanical performance. Visual inspection based on the colour changes of the thin films showed quinone (yellow) formation of the irradiated films of BP and BPC of VOP and WOP. As a conclusion, the effect of prolonged exposure to UV light, in general promotes photo degradation for BP but BPC gives slower chemical modification. The innovative biopolymer composite were successfully designed and developed by adding the TiO2 as UV stabilizer to reduce the photo-degradation of the biopolymer.